Research progress of metal-organic frameworks in implant surface modification - NI Hao, LI Danxue (Kouqiang yixue, 2025)
As oral implant technology advances, implant prostheses have become an important option for restoring missing teeth. The surface properties of implants, which are a crucial component of implant prostheses, have a significant influence on implant success rate. As a result, surface modification of implants to improve their biological characteristics has emerged as a research hotspot in the field of oral implants. Due to their excellent biocompatibility, high porosity and drug loading, adjustable structure and pore size, metal-organic framework materials have drawn increased attention as promising implant surface coating materials. This paper reviews the research on metal-organic framework materials in implant surface coatings in recent years, and provides a reference for their further application in implantology.